Continuous Passive Motion Machine for Elbow Rehabilitation - Hamzah Hussein Mohammed Al-Almoodi; Norsinnira Zainul Azlan; Ifrah Shahdad; Norhaslinda Kamarudzaman (International Journal of Robotics and Control Systems, 2021)
Continuous Passive Machines (CPM) facilitate patients in eliminating joint stiffness after surgery and lead to a faster and more efficient recovery. However, many previous CPM machined are mechanically complicated, expensive, and lack a user interface. This paper presents a new CPM machine for elbow flexion-extension and forearm pronation-supination. The machine is simple, low-cost, and equipped with Graphical User Interface (GUI). Its mechanism is designed so that it can be used on the left or right arms interchangeably. It is developed using aluminum, perspex, and steel rods. The electrical part of the machine consists of Arduino Uno to drive the motors and a potentiometer to measure the patients’ Range of Motion (ROM). The GUI for setting the exercise parameters and monitoring the patients’ progress has been developed using MATLAB software. The experimental results show that the machine has successfully provided the repetitive desired motions. The machine realizes elbow flexion-extension and forearm pronation-supination movements with 0ᵒ-135ᵒ and 0ᵒ-90ᵒ ranges of motion (ROM), respectively. The machine is also capable of increasing the elbow joint’s ROM by 5ᵒ increments for the therapy. The results show that the machine has the potential to be used in hospitals and rehabilitation centers.